2011
DOI: 10.1021/ma201865s
|View full text |Cite
|
Sign up to set email alerts
|

Multicompartment Block Polymer Micelles

Abstract: Multicompartment micelles are an intriguing class of self-assembled aggregates with subdivided solvophobic cores. They have been subject to extensive research in part due to their unique morphological and sequestration properties as a result of multiple distinct chemical environments being in close proximity within one nanostructure. Multicompartment micelles hold potential for use in various applications that include the therapeutic delivery of multiple incompatible drug payloads. The present Perspective revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
415
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(429 citation statements)
references
References 156 publications
5
415
0
2
Order By: Relevance
“…90,107 Polypeptide-Based l-ABC Star Copolymers Another emerging polymer topology are miktoarm l-ABC star terpolymers. Lodge has demonstrated multicompatment micelle formation in aqueous media for synthetic star terpolymers, 15,[120][121][122] yet research in the area of peptide-containing l-ABC systems has been limited to bulk self-assembly properties. 103,104 In one such study, PS-PI-poly(e-tert-butyloxycarbonyl-L-Lysine) (PS-PI-PBLL) was found to self-assemble into lamellar nano-domains of amorphous PS and PI oriented perpendicular to liquid crystalline (smectic) PBLL domains (Fig.…”
Section: Feature Articlementioning
confidence: 99%
“…90,107 Polypeptide-Based l-ABC Star Copolymers Another emerging polymer topology are miktoarm l-ABC star terpolymers. Lodge has demonstrated multicompatment micelle formation in aqueous media for synthetic star terpolymers, 15,[120][121][122] yet research in the area of peptide-containing l-ABC systems has been limited to bulk self-assembly properties. 103,104 In one such study, PS-PI-poly(e-tert-butyloxycarbonyl-L-Lysine) (PS-PI-PBLL) was found to self-assemble into lamellar nano-domains of amorphous PS and PI oriented perpendicular to liquid crystalline (smectic) PBLL domains (Fig.…”
Section: Feature Articlementioning
confidence: 99%
“…Upon addition of a selective solvent for one of these blocks, core-shell nanoparticles are formed which have an insoluble core and solvated corona. 1 The solution self-assembly of BCPs has enabled the preparation of different micelles morphologies, including spherical 2,3 , vesicles 2,4 , cylinders [5][6][7] , and platelets 8,9 . These selfassembled materials are of interest for a range of applications from drug delivery [10][11][12][13] to composite reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, amphiphilic copolymers have attracted considerable interest owing to their unique self-assembly and phase behavior properties in solution and their numerous practical applications in surfactants, flocculating agents, drug delivery systems, and biomedical field [1][2][3]. Amphiphilic copolymers composed of hydrophilic and hydrophobic segments can form micelles with a hydrophobic compact inner core and a hydrophilic swollen outer shell in aqueous media [4,5].…”
Section: Introductionmentioning
confidence: 99%